Implementing The Minimum Service Standards Policy for Fulfilling Neglected Elderly’s Basic Needs Through Institutional Based Social Rehabilitation - Asri Muninggar Sari; Bambang Shergi Laksmono (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
The increasing elderly population in Indonesia, projected to reach 25% by 2050, presents significant demographic challenges. Currently, elderly individuals make up 11.75% of the population (Direktorat Kesejahteraan Rakyat, 2023). In response, the government has enacted policies, such as the Elderly Welfare Law, to ensure their welfare (Law Number 13 of 1998). However, many elderly still face neglect, struggling with disabilities, basic needs, and lack of familial support, exacerbated by poverty and diminishing family values (Sulastri & Humaedi, 2017). This study explores the implementation of Minimum Service Standards (MSS) in the social sector for neglected elderly in West Java, focusing on the Griya Lansia Elderly Service Center. Utilizing a qualitative approach with descriptive research methods and the data were collected through in-depth interviews and observations. The findings reveal that the implementation of MSS successfully meets all aspects outlined by Edward III (1980), Van Meter & Van Horn (1975), and Rondinelli & Cheema (1983), including environmental conditions, resource availability, and implementer capabilities. Basic services provided include food, clothing, accommodation, health supplies, various forms of guidance, and assistance with national identity registration and family services, effectively addressing the basic needs of neglected elderly individuals.